PENGARUH MODEL PEMBELAJARAN KOOPERETIF NUMBERED HEAD TOGETHER TERHADAP HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN DI SD - Yanti, Teresia; Sabri, Tahmid; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem in this research is "How is the influence of cooperative learning model type Numbered Head Together to the learning outcomes of V Student Education of Grade V of State Elementary School 36 Pontianak Selatan". This study aims to determine how big the influence of cooperative learning model type numbered head together toward the learning outcomes of Vocational Education Students Class V State Elementary School 36 Pontianak Selatan. The research method used was experiment with quasi experimental desing research with non-equivalent control group desing. Population in this research is all student of class V Elementary School 36 Negeri Pontianak Selatan with sample 20 student (VA) .Teknik data collection used is measurement by means of data collection in the form of test result of student learning in the form of multiple choice. The learning outcomes obtained by the experimental class average of 73.5. The result of the hypothesis of separated variance is obtained tcount 2,514 and ttable (? = 5% and dk = 38) equal to 1,685 indicate that tcount is bigger than ttable hence h shall be accepted. This means that there is influence of student learning outcomes are taught by applying the model of learning numbered head together with students who taught without applying the model of learning numbered head together and effect size obtained 0,56 with the criteria are. Keywords: cooperative learning model type numbered head together, learning outcomes, civic education.